The role of spatial distance to hazards in risk perception: A systematic literature review - Liu L; Feng Z; Paes D; Lovreglio R (Elsevier Ltd, 2026)
Introduction: The rapid change in climate and advancement in new materials and technologies are reshaping risk landscapes with more frequent and severe hazards, emergencies, and disasters. Spatial proximity to those hazards critically shapes risk perception, influencing safety decisions and behaviors. Though a few studies have investigated how people perceive and respond to risks based on different spatial exposure to hazards, the role of spatial distance in shaping risk perception remains conceptually fragmented. This systematic review aims to: (a) evaluate methodological approaches to distance and risk perception assessment; (b) examine human factors mediating proximity effects; and (c) identify patterns in distance-risk perception relationships. Method: A PRISMA-guided analysis of 54 studies from Scopus and Web of Science was conducted to examine the literature. Results: This review identified three distance-risk perception patterns: (a) increased risk perception with proximity (45 studies), largely attributed to sensory salience; (b) reduced perception near hazards (6 studies), linked to habituation; and (c) non-linear patterns (3 studies), influenced by familiarity and motivational trade-offs. The reviewed studies applied different methods to categorize and measure the distance to hazards, including Euclidean distance, zone-based classification, and real-time sensing. Risk perception was evaluated through diverse methodologies such as surveys, validated Likert-type scales, behavioral observations, and technology-driven tools like virtual reality simulations and physiological monitoring. This review also finds that human factors, such as age, gender, education, income, and prior experience, moderate proximity effects, with older adults and women exhibiting stronger sensitivity. Practical applications: This study contributes a unified overview of methodological variation and perceptual outcomes, offering new insight for risk communication, policy design, and hazard management.